Strength Training and its Effect in Some Biochemical Variables in the High Jumping of Advanced Players - Rashid Hameed, Intisar; Sadiq Dhiab, Ali; Saeed, Sarmad (International Journal of Psychosocial Rehabilitation, 2020)
The study of biomechanical indicators in the arc of the run and the upgrading stage is one of the important variables that affect the nature of the upgrading and thus affect the result of the race due to the importance of these stages and the consequent variables during the last steps. That’s why the jump trainings based on assistant means or body weight positively affect the step-time for each of the three steps in the acceleration arc. As well as, it focuses on the momentary strength of each step at this stage. It also significantly affects the speed of motor performance to suit the activity in which the runner needs to perform perfect steps with high flow in order to convert the horizontal speed to a vertical one. This is achieved through producing high instantaneous power in a short time to achieve a perfect elevation. Those trainings must be built according to real indicators based on scientific results to know the nature of these time characteristics and the range of their impact on the variables of the last three steps and upgrading, because these variables depend on performance and accuracy and need stability in performance during attempts. Therefore, some biomechanical variables are found for the three steps and the stage of upgrading through the use of video graphing, kinetic analysis, and preparing special trainings to develop these variables in order to solve this problem that faces the players of the country right now. The research was applied to a group of high-jump players from the country for the (6) advanced-level players, and the results of the preceding and following tests were compared. The researchers concluded that the exercises that were performed by using the means and equipment according to the performance and that were used within the strength exercises are effective in developing the pushing time at the moments of contact for the last three steps and the stage of upgrading. In the same way, they are effective in the right-time strength of the performance nature, which helped in the frugality of time, the force spent correctly, and the interconnection of the parts of the correct performance of these variables in the last three steps. This is reflected in the stage of upgrading and led to its development.